Harry Potter and the prisoner of azkaban - Rowling, J. K. (New York : Scholastic Inc, 2000)
During his third year at hogwarts schools for withcraft and wizardy Harry Potter must confront the devious and dangerous wizard responsible for his parents' death.
Keywords: WIzard -- fiction; Magic -- fiction; Schools -- Fiction; England -- Fiction